Respuesta :

Answer: Rewrite equations:

5x+y=−13;6x+6y=−6

Step: Solve5x+y=−13for y:

5x+y=−13

5x+y+−5x=−13+−5x(Add -5x to both sides)

y=−5x−13

Step: Substitute−5x−13foryin6x+6y=−6:

6x+6y=−6

6x+6(−5x−13)=−6

−24x−78=−6(Simplify both sides of the equation)

−24x−78+78=−6+78(Add 78 to both sides)

−24x=72

−24x

−24

=

72

−24

(Divide both sides by -24)

x=−3

Step: Substitute−3forxiny=−5x−13:

y=−5x−13

y=(−5)(−3)−13

y=2(Simplify both sides of the equation)

Answer:

x=−3 and y=2

Step-by-step explanation: